Enhancing fluorescent protein photostability through robot-assisted photobleaching. Issue 7 (13th June 2018) - Wiens, M. D.; Hoffmann, F.; Chen, Y.; Campbell, R. E.
Abstract : Improving fluorescent proteins through the use of directed evolution requires robust techniques for screening large libraries of genetic variants. Abstract : Improving fluorescent proteins through the use of directed evolution requires robust techniques for screening large libraries of genetic variants. Here we describe an effective and relatively low-cost system for screening libraries of fluorescent protein variants for improved photostability in the context of colonies on a Petri dish. Application of this system to the yellow fluorescent protein mCitrine, led to the development of Citrine2 with improved photostability and similar high fluorescent brightness. The photobleaching robot was constructed using a Lego Mindstorms Ev3 set and a xenon arc lamp, which together create even and high irradiance over an entire Petri dish through patterned illumination.